ASSESSMENT OF VASCULAR ENDOTHELIUM CONDITION IN PATIENTS WITH RENAL NEPHROSCLEROSIS DUE TO CHRONIC PYELONEPHRITIS - Shukurova Umida Polatovna (Scholars Digest Publishing, 2024)
It is known that modern diagnostic methods allow visualization of the state of the kidney parenchyma, but each of the described examination methods has its own shortcomings. In addition, in patients with chronic kidney disease, some parameters of renal blood flow significantly change and are misinterpreted, which does not allow to reliably determine the presence and degree of sclerosis of the renal parenchyma. The article covers information on determining the prognostic significance of markers for predicting the degree of damage to kidney structures during the treatment stages of patients with nephrosclerosis on the basis of chronic pyelonephritis.
Keywords: diagnostic methods, endothelial dysfunction, vasomotor, chronic pyelonephritis, thrombophilic, adhesive, renal fibrosis, angiogenicity.